2019
DOI: 10.26434/chemrxiv.8006789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZIF-8 Degrades in Cell Media, Serum, and Some—But Not All—Common Laboratory Buffers

Abstract: <p>The emergence of drug delivery using water stable metal-organic frameworks has elicited a lot of interest in their biocompatibility. However, few studies have been conducted on their stability in common buffers, cell media, and blood proteins. For these studies, single crystal ZIF-8 approximately 1 um in diameter were synthesized, incubated with common laboratory buffers, cell media, and serum, and then characterized by PXRD, IR, DLS, and SEM. Time-resolved SEM and PXRD demonstrate that buffers contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…phosphate-buffered saline, PBS). 18,24,25 ZIF-8 is a crystalline microporous material with sodalite (sod) topology that is synthesized by mixing aqueous solutions of HmIM and Zn 2+ . [26][27][28] However, by varying the synthetic conditions, other topologies can be obtained (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…phosphate-buffered saline, PBS). 18,24,25 ZIF-8 is a crystalline microporous material with sodalite (sod) topology that is synthesized by mixing aqueous solutions of HmIM and Zn 2+ . [26][27][28] However, by varying the synthetic conditions, other topologies can be obtained (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another important property that needs to be considered for the drug release performance of MOFs is how the material degrades under physiological conditions. [30][31][32][33] Ruyra et al demonstrated that several nanoMOFs (e.g. UiO-67, ZIF-7, HKUST-1) become amorphous or decompose releasing cations when exposed to the cell culture medium (Dulbecco's modified Eagle's medium).…”
Section: Introductionmentioning
confidence: 99%
“…9 In another study, Luzuriaga et al showed that ZIF-8 can degrade in several buffer solutions suggesting that this aspect should be taken into account for biotechnological applications. 33 However, the mechanism of degradation of ZIF-8 particles in PBS has not been fully elucidated and the related kinetics of decomposition remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we probe Dox (in the form of doxorubicin hydrochloride) loading and release using UiO-66, which has been studied intensely for drug delivery, 59 as a small-pore MOF (ZIF-8 has been shown to have poor stability to pH < 7 60 and in certain biological buffers 61 , 62 ) and MIL-101(Cr), in which BDC linkers connect trimeric Cr 3 O(RCO 2 ) 6 (H 2 O) 2 X (X = a monoanion) SBUs into the mtn topology with pore apertures of 12.0, 14.7, and 16.0 Å in diameter, 63 as a large-pore MOF. There are a small number of studies into Dox uptake and delivery by MIL-101(Fe) and derivatives, 34 , 64 , 65 , 66 one of which is clearly indicative of pore loading, 67 but none into MIL-101(Cr).…”
Section: Introductionmentioning
confidence: 99%